2021
DOI: 10.1186/s12964-021-00786-z
|View full text |Cite
|
Sign up to set email alerts
|

Beclin1 controls caspase-4 inflammsome activation and pyroptosis in mouse myocardial reperfusion-induced microvascular injury

Abstract: Background Myocardial reperfusion injury is often accompanied by cell death and inflammatory reactions. Recently, pyroptosis is gradually recognized as pivotal role in cardiovascular disease. However, little is known about the regulatory role of beclin1 in the control of caspase-4 activation and pyroptosis. The present study confirmed whether beclin1 regulates caspase-4 mediated pyroptosis and thereby protects Human Cardiac microvascular endothelial cells (HCMECs) against injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
(34 reference statements)
2
28
0
Order By: Relevance
“…Inhibition of the FUNDC1-mediated mitophagy in CMECs by the nuclear receptor subfamily 4 group A member 1 (NR4A1) [116] or receptor-interacting protein kinase 3 (Ripk3) [117] exhibited the disturbed mitochondrial homeostasis, upregulated the expression of EC-derived proinflammatory and adhesive factors, enhanced endothelial apoptosis, and provoked CMD in cardiac I/R injuries. In addition, enhancing autophagy through Beclin1 overexpression in CMECs exhibited suppressed NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome activation by promoting tumor necrosis factor-alpha-induced protein 3 (TNFAIP3) [118] and inhibited caspase-4 inflammasome activation [119]. Thus, it resulted in a reduced IL-1β level and an increased animal survival upon myocardial I/R injuries.…”
Section: Coronary Endothelial Autophagy In Obstructive Cad (Stable Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the FUNDC1-mediated mitophagy in CMECs by the nuclear receptor subfamily 4 group A member 1 (NR4A1) [116] or receptor-interacting protein kinase 3 (Ripk3) [117] exhibited the disturbed mitochondrial homeostasis, upregulated the expression of EC-derived proinflammatory and adhesive factors, enhanced endothelial apoptosis, and provoked CMD in cardiac I/R injuries. In addition, enhancing autophagy through Beclin1 overexpression in CMECs exhibited suppressed NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome activation by promoting tumor necrosis factor-alpha-induced protein 3 (TNFAIP3) [118] and inhibited caspase-4 inflammasome activation [119]. Thus, it resulted in a reduced IL-1β level and an increased animal survival upon myocardial I/R injuries.…”
Section: Coronary Endothelial Autophagy In Obstructive Cad (Stable Ca...mentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells11132081/s1, Table S1: Mechanistic studies implicating endothelial autophagy or mitophagy in cardiovascular diseases [93,105,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][130][131][132][133][149][150][151][152][153][154][155][156][157][158][159][160][166][167][168][169][170]181,[184][185][186][187]…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…NLRP3 markedly promotes pyroptosis in the progression of AMI, knockdown of NLRP3 attenuated cardiomyocyte pyroptosis and significantly decreased the infarct size, as evidenced by decreased expression levels of ASC, pro-Caspase-1, Caspase-1-p10, GSDMD, cleaved GSDMD, and IL-18 ( 45 ). Becn1-driven autophagy is a protective response in the heart during I/R, Becn1 overexpression suppressed Caspase-4 inflammasome activation and pyroptosis, alleviated microvascular damage, reduced infarct size, and mitigated cardiac inflammation and cell death ( 97 ). The recent research showed that activation of SIRT1 by inhibition of miR-29a inhibited oxidative stress, pyroptosis and protect I/R injury ( 98 , 99 ).…”
Section: Role Of Pyroptosis In Cardiac Remodelingmentioning
confidence: 99%
“…Becn1 overexpression increased Ischemia-reperfusion mouse survival and decreased the levels of serum LDH and CK. BECN1 attenuated F4/80+ macrophages and CD11b+ neutrophils infiltration in the heart ( 97 ). Meanwhile, myocardial fibrosis was markedly ameliorated, the collagen was decreased through suppressing GSDMD-mediated pyroptosis when PVT1 knockdown ( 96 ).…”
Section: Potential Clinical Applications Of Pyroptosis To Ameliorate ...mentioning
confidence: 99%
“…16 Currently, gasdermins consist of six members: gasdermins A, B, C, D, E, and DFNB59. 17 Most GSDMs members have conservative N-and C-terminal structures and there are differences in the linker region. Activated caspase-1 or caspase-11/4/5 are cleaved in the linker in GSDMD to release the N-terminus with pore-forming domain (PFD) activity.…”
Section: Pyroptosis and Gasdermins Familymentioning
confidence: 99%